The relationship of the application of responsibility accounting between forensic accounting and financial performance control in companies listed on the Palestine Stock Exchange - Mohanna, Mohammad Fathi (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the relationship of the application of responsibility accounting between forensic accounting and financial performance control in the companies listed on the Palestine Stock Exchange. Palestine, and a sample of 300 male and female employees was selected, and the (SPSS) statistical program was used to analyze the study hypotheses.The study reached several results, the most important of which are: There is a direct correlation with a statistical significance between the application of responsibility accounting and forensic accounting and controlling the financial performance of companies listed on the Palestine Exchange, and it focused on the areas of effective administrative reports, effective planning budgets, and inspections and investigations, and one of the most important recommendations of the study Develop a proposal to implement the responsibility and forensic accounting system in Palestinian companies that do not apply it, follow-up the stages of application of this system and evaluate it comprehensively, and establish a follow-up unit for its implementation.
Keywords: Responsibility accounting; forensic accounting; financial performance